Developing a Manualized Occupational Therapy Diabetes Management Intervention: Resilient, Empowered, Active Living With Diabetes. (July 2015) - Pyatak, Elizabeth A.; Carandang, Kristine; Davis, Shain
This article reports on the development of a manualized occupational therapy intervention for diabetes management. An initial theoretical framework and core content areas for a Stage 1 intervention manual were developed based on an in-depth needs assessment and review of existing literature. After evaluation by a panel of experts and completion of a feasibility study, the intervention was revised into a Stage 2 manual in preparation for a randomized study evaluating the intervention's efficacy. In developing the initial manual, we delineated core theoretical principles to allow for flexible application and tailoring of the intervention's content areas. Expert panel feedback and feasibility study results led to changes to the intervention structure and content as we developed the Stage 2 manual. Through describing this process, we illustrate the dynamic evolution of intervention manuals, which undergo revisions due to both theoretical and practical considerations at each stage of the research-to-clinical practice pipeline.